Phenolic contents, antimicrobial and antioxidant activity of Olea ferruginea Royle (Oleaceae) - Ansar Mehmood; Ghulam Murtaza (BMC, 2018)
Abstract Background Olea ferruginea Royle (Oleaceae) has long been used as an important ethnomedicinal plant to cure fever and debility, toothache, hoarseness, throatache and skeleton disorders. In this study, phenolic contents, antimicrobial and antioxidant activities of leaf and bark extracts (chloroform, ethanol and methanol) of O. ferruginea were evaluated. Methods Total phenolic contents were determined by Folin-Ciocalteu Spectrophotometric method. Antimicrobial activity was examined against Bacillus subtilis and Staphylococcus aureus (Gram positive), Escherichia coli (Gram negative), Candida albicans and Sccharomyces cerevisiae (yeas strains) by disc diffusion method. Antioxidant activity was observed through DPPH assay. Results The higher phenolic content was found in bark extract (376 μg/mg) of O. ferruginea. Chloroform extracts was found inactive against tested microorganisms while ethanol and methanol extracts showed pronounced inhibitory activity against both gram positive and gram negative bacteria. Only methanol extract of leaves inhibited the yeast strains. None of the bark extract inhibited the growth of tested yeast strains. The zones of inhibition formed by plant extracts were compared with zones of inhibition of available reference antibiotic discs such as tetracycline, ciprofloxacin and nystatin. Higher antioxidant activity was observed with methanol extracts of leaves and bark of O. ferruginea. Conclusion These findings show that O. ferruginea has potential antimicrobial and antioxidant activities. This study suggests a possible application of olive leaves and bark as sources of natural antimicrobial and antioxidants.